Upaya Meningkatkan Hasil Belajar Matematika melalui Penggabungan Metode Drill dan Demonstrasi Siswa Kelas I-B MIN Wonosari Tahun Pelajaran 2016/2017 - Sri Kusrini (Jurnal Pendidikan Madrasah, 2018)
The purpose of this research is to know the results of the students before the use of drill and method demonstrations and whether the use of the methods of drill and demonstrations at learning math can improve student learning outcomes. This research is the research of class act, so that the area studied was limited to the class that has the specified class i. B MIN School number of students with as many as 18 students. Data taken through observation, documentation, and test. The results of the analysis of the research shows that students learn math, yield is still low, it can be known from the results of the evaluation of the initial tests with the value of the KKM assigned there are only 4 students who scored above the KKM or around 22% with an average rating of 67.3. After done actions there is an increase of any cycle and cycle I retrieved the result value of the students above the KKM is as much as nine children or about 55.5% with an average score of 71.6 and at the end of the cycle II obtained the result value of the students above 16 KKM children or approximately 90.5% with an average rating of 81.9, then it can be inferred that the merging method of drill and demonstrations can enhance the results of learning math students in grades I. B MIN Wonosari.